Pemanfaatan Origami dan Mural Pohon Semangat untuk Menguatkan Resiliensi Belajar di Sanggar Lentera Anak Bali - Helmy Syakh Alam; Eka Grana Aristyana Dewi; Muhammad Heisyan Aleandro; I Made Yuda Kusuma; I Putu Angga Pratama Putra; Putu Rahadi Sukamembah; Ignasius Elsington Jemalu (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Marginalized children are prone to developing a fixed mindset that hinders their learning persistence. This community service program aimed to strengthen the learning resilience of children at Sanggar Lentera Anak Bali through swan origami activities and a Pohon Semangat (Spirit Tree) mural. Using a descriptive participatory design, 20 participants aged 7–17 engaged in a two-hour session consisting of growth mindset psychoeducation, a structured failure simulation through origami folding, collaborative games, and commitment mural creation. Observational, interview, and documentation data were analyzed thematically. Results indicated that 90% of children shifted their verbal response from